Effects of Physical Activity on Asthma Patients - A Literature Review - Marchwińska-Pancer, Aleksandra; Emilia Bolesta-Okuniewska; Konrad Borowski; Julia Ceryn; Katarzyna Kopeć; Paweł Michalak; Oskar Pastuszek; Maja Radziwon; Anna Wicher (Quality in Sport, 2026)
Introduction. Asthma is a heterogeneous chronic respiratory disease characterized by chronic airway inflammation and variable airflow limitation. Historically, patients were discouraged from engaging in physical activity (PA) due to the prevalence of Exercise-Induced Bronchoconstriction (EIB). However, emerging evidence suggests that sedentary behavior and obesity are significant contributors to poor disease control and diminished quality of life in asthmatic populations. Aim. This review aims to evaluate the relationship between regular physical activity and asthma pathophysiology, specifically assessing how exercise influences clinical outcomes. Methods. A systematic review of current literature was conducted, focusing on original research, as well as systematic reviews and meta-analyses that measure the physiological response to aerobic and resistance training in asthma patients. Results. The review indicates that regular physical activity is associated with improved asthma control, enhanced lung function, and a reduction in systemic inflammation. Despite these benefits, a significant gap remains in the literature regarding the dose-response relationship of exercise. There is currently no definitive consensus on the optimal frequency, intensity, or type of physical activity tailored to specific asthma phenotypes. Conclusion. Physical activity is a vital component of asthma management that counteracts the risks associated with a sedentary lifestyle. While the physiological benefits are evident, further research is required to establish standardized exercise prescriptions to maximize therapeutic outcomes for all patients.